Informalidad laboral y brecha salarial entre trabajadores formales e informales en la Zona Central del Perú; Labor informality and wage gap between formal and informal workers in the Central Zone of Peru - Marco Antonio Arroyo Yupanqui; Germán Ccencho Pari; Juan Carlos Pérez Ticse (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– The objective of the study is to analyze the wage gaps between formal and informal workers in the Central Zone of Peru, since there is a high presence of informality in approximately more than 75.0 % of the economically active population, that is, three out of four people are informal in Peru in spite of the facilities granted by the state for formalizations. In relation to the above, the objective was to analyze the divergences in the wage gaps between formal and informal workers in the central zone of Peru using data from the National Household Survey (ENAHO) and a methodology established by Heckman, Mincer and Oaxaca. The results show that lack of education accounts for approximately 30.9% of the wage differences between formal and informal wage earners. Having incomplete primary education increases earnings by about 42.0% for formal and 52.9% for informal workers compared to those with complete education, given the majority of workers have primary and secondary education levels in the data obtained. In the Oaxaca model, lack of education contributes to approximately 23.3% of the wage differential between formal and informal workers.
Keywords: E24; J31; J30; 330; Informality; salary; gap-labor; Peru